AI-driven service quality and customer engagement: The mediating role of digital empathy and cognitive absorption - Mari , Iqrar Hussain; Iqbal , Azhar; Khan, Zahid Nawaz (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
The aim of this study is to investigate how AI-driven service quality (AISQ) influences customer engagement (CE) in the e-commerce industry in Pakistan. This study examines the mediation of digital empathy (DE) and cognitive absorption (CA). It concerns discovering how AI-driven service quality affects customer interactions through emotional and cognitive processes. Through an online survey, data were collected from 321 e-commerce clients in Pakistan. The current study used convenience sampling. A five-point questionnaire was used for data collection. The statistical tool SPSS 22.0 was used for correlation and regression analysis. The conceptual framework was built on the Technology Acceptance Model (TAM) and the Trust-Commitment Theory (TCT) to determine the association among AISQ, DE, CA, and CE. The proposed hypotheses and their mediation effects were tested using Structural Equation Modelling (SEM). The findings of the present study indicate that AISQ has a positive impact on CE. DE and CA play an important role in mediating this relationship. The results of this study show that when customers perceive AI-based services as empathetic and interesting, they are more likely to become engaged with an e-commerce platform. This paper is a contribution to the research on AI and customer behaviour, as it reveals that DE and CA are significant intermediate variables between AISQ and CE. The results are valuable to e-commerce leaders in Pakistan, helping them improve customer engagement and loyalty through emotive, compelling AI solutions.